Multi-antenna diversity receiving scheme for mobile communication system in high-speed railway - Wan-tuan LUO; ANGXu-ming F; Meng CHENG; Ya-jun ZHAO (Tongxin xuebao)
Under the signal model of differential modulation and demodulation, two multi-antenna diversity receptions (linear combiner and statistic combiner) were proposed, and then the effective diversity reception scheme of train-to-ground wireless broadband communication for high-speed railway scenarios was concluded. Mathematical analysis and simulation results indicate that by increasing the diversity number, the proposals can reduce the error floor because of high mobility. The performance of linear combiner is much better than that of statistic combiner, but the re-ceiver complexity of linear combiner is also higher than that of statistic combiner. In term of practical application, the tradeoff between performance and complexity must be made according to the quality of service (QoS) requirements.